Big Book Media with Science Learning Content Based on Balinese Local Wisdom for Fifth Grade of Elementary School Students - Parwati, Ni Ketut Mega Resi; Rati, Ni Wayan; Margunayasa, I Gede (Jurnal Pedagogi dan Pembelajaran, 2024)
The low motivation to learn students is caused due to several factor both from the teacher and students. Through the application of Big Book can increase student motivation. The study aims to develop a Big Book with the science learning based on Bali local wisdom for five grade of elementary school which has been tested for authenticity, practicality, and effectiveness in increase student motivation. This research is guided by the ADDIE development model which consists of the analysis stage, design stage, development stage, implementation stage, and evaluation stage. The study subject includes design experts, media experts, materials experts, practitioners’ experts numbered 1 teachers, and students numbered 23 students. The data collection method is by asking questions to the subject. The percentage of evaluation results of design experts is: 89.28% with very good qualifications, media experts: 85.89%, very good qualifications, material experts: 95.00%, very good qualifications, answers from practitioners: 92.05%, qualifications very good and response from students: 93.85%, very good qualifications. The results of the validity test using the correlated t test method found significance (Sig. 2-tailed) 0.000 < 0.05, so H0 was rejected and Ha was accepted. Based on the results of the analysis, the Big Book with the science learning based on Bali local wisdom to valid and practical to use in learning, as well as effective in motivating students to learn.